131I- und 99mTc-Uptake in fokalen Schilddrüsenautonomien - Happel, Christian; Kranert, W. Tilman; Bockisch, Benjamin; Korkusuz, Hüdayi; Grünwald, Frank (Nuklearmedizin - NuclearMedicine, 2016)
Germany has developed into a country with a nationwide largely sufficient iodine supply due to improved alimentary iodine supply. The reduction of iodine uptake in focal autonomies induced by reduced iodine avidity was evaluated by Gotthardt et al. 2006, showing a significant decline of pertechnetate uptake up to the year 2004. Aim: This study was intended to carry this investigation forward to the present day to analyze the course of a conjectural stabilization of iodine uptake values. Patients, material, methods: 283 patients who underwent radioiodine therapy for focal thyroid were analyzed retrospectively. Pertechnetate uptake was measured scintigraphically, thyroid volume sonographically and iodine uptake by iodine uptake test. The uptake percentage in the autonomous volume was correlated with autonomous volume and the resulting values tracked over a time period of seven years. Results : Mean thyroid volume ranged from 24 to 29 ml, autonomous volume from 7.2 to 9.4 ml. Pertechnetate uptake ranged from 0.2 to 0.25%/ml autonomous volume. Iodine uptake values ranged from 3.2 to 4.2%/ml autonomous volume. None of the changes observed were statistically significant (all p>0.05). Conclusion: Prophylactic measures towards improvement of the general public´s iodine supply in Germany had led to a decline of pertechnetate and iodine uptake in the thyroid up until the turn of the millennium. The here presented data show a stabilization of 99mTc-Uptake. Our study could also show that actual iodine uptake has stabilized at a steady level over the preceding seven years.
Keywords: Technetium uptake; iodine supply; benign thyroid diseases; radioiodine therapy